Presidential Campaign Authority in The General Election Law - Muhammad Salman Alfansuri Jacob; Firzhal Arzhi Jiwantara; Herni Ramayanti; Sri Chatun; Esa Arung Syuhada (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The President's Authority to Campaign during the General Election has recently become an interesting topic of discourse among the public. Some people think that the President should not campaign to maintain the neutrality of elections, the President's dignity, and so on. However, on the other hand, the public thinks that it is okay for the President to campaign because basically it is not the norm in the laws and regulations that has been violated. Therefore, this research aims to examine the President's authority to campaign in Law Number 7 of 2017 concerning General Elections. This research is a qualitative research with a normative approach that uses legislative regulations as the main focus to elaborate and explain comprehensively the authority of the President's campaign in the General Election Law. The data used in this research is secondary data that researchers obtained from statutory regulations, scientific journals, books, credible websites, and a number of other sources that are commonly used in every research. These data were analyzed using grammatical and teleological legal interpretation methods. The result in this articel show 1. There are two different opinions, namely those who agree with the president's campaign with the argument of maintaining ELECTION neutrality, potentially causing abuse of power, and maintaining presidential ethics. But on the other hand, they think it's okay because no rules have been violated. 2. Article 281 paragraph 1 of Law Number 7 of 2017 concerning General Elections regulates the President's ability to campaign as long as he does not use state facilities and takes leave. However, this article was interpreted differently by Bivitri Susanti because it relates to the President who will nominate again and the President must be registered in the campaign team. Apart from that, Zainal Arifin Mukhtar also has the same opinion that the President's campaign could cause legal complications and could potentially lead to the practice of nepotism. 3. The researcher does not agree with the two constitutional experts because there is an inconsistency in Bivitri Susanti's argument that initially the president was not allowed to campaign by interpreting market 281 paragraph 1 as relating to the incumbent President, but in the next sentence it seems to allow it by requiring the President to be included in the campaign team. Regarding Zainal Arifin Mukhtar's opinion, researchers consider that campaigning and nepotism are two very different things. Can campaigning is something that has not happened and is stated in the laws and regulations, whereas nepotism is something that has already happened and needs to be proven first and it does not necessarily mean that the President campaigning is nepotism. The researcher adheres firmly to the principles of Nullum Delictum, Nulla poena sine praevia lege poenali